Little black book of stories - Byatt, A. S. (Antonia Susan), 1936- (London : Vintage, 2004)
A.S. Byatt's anthology departs from her normal subject matter. As well as giving the reader a magical thrill the stories also send shivers down the spine. By turns funny, spooky, sparkling, and sad, these tales will linger in your mind forever.
The thing in the forest -- Body art -- A stone woman -- Raw material -- The pink ribbon.
Originally published : London: Chatto & Windus, 2003.
Keywords: English fiction